2021
DOI: 10.1021/acsomega.0c05260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO and CO2 on the Removal of Elemental Mercury over Carbonaceous Surfaces

Abstract: Coal gasification is a popular method for the optimization of coal utilization and the reduction of environmental pollutant emissions. However, the reductive atmosphere of its products is disadvantageous for removing elemental mercury (Hg0). Activated cokes (AC) was employed in this work for mercury capture in a reducing atmosphere. The high-temperature heating decreases the mercury-removal capability of carbon sorbents because the carbonaceous surface is becoming oxygen-depleted and micropore-decreased after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…It can be seen that the oxy-fuel gas is not conducive to the adsorption of mercury by the adsorbent, and the main reason may be that Hg 0 (2.97 Å) and CO 2 (3.30 Å) have similar kinetic diameters, which make their adsorption behavior in pores similar. Therefore, Hg 0 competes with CO 2 for physical adsorption. , It can be seen from Figures and that when the temperature rose from 150 to 350 °C, the mercury breakthrough rate increased and the mercury uptake decreased. The results showed that high temperature could inhibit the adsorption of mercury.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It can be seen that the oxy-fuel gas is not conducive to the adsorption of mercury by the adsorbent, and the main reason may be that Hg 0 (2.97 Å) and CO 2 (3.30 Å) have similar kinetic diameters, which make their adsorption behavior in pores similar. Therefore, Hg 0 competes with CO 2 for physical adsorption. , It can be seen from Figures and that when the temperature rose from 150 to 350 °C, the mercury breakthrough rate increased and the mercury uptake decreased. The results showed that high temperature could inhibit the adsorption of mercury.…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, Hg 0 competes with CO 2 for physical adsorption. 39,40 It can be seen from Figures 1 and 2 that when the temperature rose from 150 to 350 °C, the mercury breakthrough rate increased and the mercury uptake decreased.…”
Section: Resultsmentioning
confidence: 98%
“…The increase of the temperature reduces the concentration of CO and weakens the reducing atmosphere in the FR, which is conducive to the oxidation of Hg 0 . , However, some scholars have come to a different conclusion. Mendiara et al reported a lower proportion of Hg 2+ at a higher FR temperature, which is inconsistent with the findings of other scholars.…”
Section: Factors Influencing Mercury Migration In the Clc Systemmentioning
confidence: 99%